Conceptual design synthesis and optimization for new generations of combat aircraft - Siegers, Frank (Cranfield University, 1996)
A numerical design synthesis methodology for new generations of combat aircraft has been developed. It incorporates advanced technology in the form of design for low observables. Aircraft capable of being modelled with this methodology will have internal or external Weapons carriage, side mounted intakes, a straight-tapered trapezoidal wing, aft-mounted tail with the option of single or twin ns, and one or two engines with rectangular or axisymmetric nozzles. The design methodology incorporates sufficiently accurate and realistic algorithms for the calculation of the geometry and the estimation of the aerodynamic, mass and performance properties of the aircraft. The inherent flexibility of the design permits the examination of a wide range of configurations whilst maintaining the accuracy required to examine minor changes in the design requirements. A numerical optimization routine was linked to the synthesis, allowing the determination of optimum aircraft design variables for a given set of mission and performance requirements. Results were obtained showing the usefulness of this design tool for setting up parametric trend studies. The numerical accuracy, flexibility of configuration options and high level of advanced aircraft technology of this synthesis make a significant contribution to the continuing development of automated design tools.